Automatic Coordination of Internet-Connected Thermostats for Power Balancing and Frequency Control in Smart Microgrids - Saeid Bashash; Kai Lun Lee (Energies, 2019)
This paper proposes a novel feedback control strategy, so-called clock-like controller (CLC), to balance power supply and demand in smart microgrids by adjusting the setpoint temperatures of air conditioning (AC) loads. In the CLC algorithm, the grid operator communicates with the individual thermostats via the Internet and adjusts their setpoints by discrete temperature intervals (e.g., ±0.5 °C). Numerical simulations indicate that the proposed algorithm is able to deliver a smooth controllability of the aggregate AC power despite discrete temperature offsets. It can also be used for peak load shedding to mitigate the power generation cost. The CLC algorithm is then integrated into the grid frequency control problem, in which both power generators and loads in the network attempt to regulate the frequency of the system despite disturbances from demand, renewable sources, and local weather conditions. An autonomous microgrid model including a steam and a hydro generator, a solar energy source, and a large number of thermostatic loads is developed to evaluate and demonstrate the proposed method. Simulation results indicate that the AC loads with CLC algorithm can help maintain the power system frequency during extreme events when demand exceeds the maximum generation capacity available to the network. Under normal conditions, the contribution of demand-side control is marginalized by the fast responding generators, because of time delays in the frequency measurement and internet communication network.